Pharmacology of histamine receptors - Ganellin, C. R. (C. Robin); Parsons, M. E. (Michael E.) (PSG, 1982)
Pharmacology of Histamine Receptors presents a summary of the pharmacology of histamine receptors. It discusses the research and developments made in the use of histamine. It addresses the biological actions of the drug in various pathological instances. Some of the topics covered in the book are the classification of histamine receptors; mepyramine and related histamine antagonists; activity relationships of drugs acting at histamine receptors; chemical structure of histamine; effects of methyl substituents in histamine; enzymes involved in histamine metabolism; and histamine in body fluids.